The missing link between flood risk awareness and preparedness: findings from case studies in an Alpine Region - Scolobig, Anna; De Marchi, B.; Borga, M. (Natural hazards (Dordrecht), 2012)
The low risk awareness of the residents living in flood-prone areas is usually considered among the main causes of their low preparedness, which in turns generates inadequate response to natural disasters. In this paper, we challenge this assumption by reporting on the results of a sociological research in four communities exposed to flood risk in the Eastern Italian Alps. The research design included semi-structured interviews and focus groups with key local stakeholders and a standardized questionnaire submitted to 400 residents. Results revealed that residents felt both slightly worried about flood risk and slightly prepared to face an event. Considerable differences were found between the evaluations of individual subjects as opposed to overall communities. There was also a clear discrepancy between the actual adoption of household preparatory measures and the willingness to take self-protection actions. Overall, the risk awareness was significantly higher among those residents who had been personally affected by a flood in the past, were living in isolated (vs. urban) communities, in the most risky areas or had a lower level of trust in local authorities. The improvement of residents’ knowledge about their environment and the residual risk seemed to be crucial to increase risk awareness, and the same was true for the strengthening of local support networks to foster preparedness. The link between risk awareness and preparedness was not at all straightforward. Results revealed instead the complexity of residents’ perspectives, attitudes, behaviours and decisions about risk-related issues.